The ozone hole and a phase change in lower stratospheric temperature - Michael O Jonas (Zenodo, 2024)
Depletion of ozone over Antarctica was first observed in the late 1970s, and discovery of the Antarctic ozone hole was announced in the 1980s as having started in 1979. The ozone hole was defined as the area with total column ozone less than 220 Dobson units. Analysis of ozone, temperature, chlorofluorocarbon and nitrous oxide data from 1963 onwards suggests that the annual ozone minimum at the South Pole is related to lower stratospheric temperature independently of chlorofluorocarbons and nitrous oxide. There were ozone holes, ie. column ozone less than 220 Dobson Units, at the South Pole in several years before 1979 (the date that the ozone hole is reported to have first appeared) when chlorofluorocarbon concentrations were much lower than today and lower than in 1979. An early 1980s phase change in the lower stratospheric temperature at the South Pole at altitudes between 250 hPa and 100 hPa, and at some lower altitudes, coincides with a phase change in the annual South Pole ozone minimum. The phase change is not visible in chlorofluorocarbon or nitrous oxide data. This raises the possibility that, over a multi-annual or decadal timescale, lower stratospheric temperature has more effect than chlorofluorocarbons or nitrous oxide on atmospheric ozone concentration over the South Pole. Alternatively, temperature and ozone may both be reacting to some other influence